2012
DOI: 10.1111/j.1469-7998.2011.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and altitudinal influences on the home range and movements of common wombats in the Australian Snowy Mountains

Abstract: Many animals throughout the world are excluded from areas because of seasonal snow cover. The aim of this study was to determine how snow influences the home range use and movements of the common wombat, a large burrowing mammal that remains active in the subalpine zone of the Australian Snowy Mountains throughout winter but is not resident in the alpine zone (above treeline). Global positioning system collars were deployed on wombats to monitor nightly movements continuously over both the winter and non‐winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…Differences in the selection of resources by individuals may be largely dependent on the availability or quality of the habitat (Gustine et al . ), and this was also reflected in the larger size of home ranges of wombats at higher altitudes (Matthews & Green ). The general geographic location of the wombat's home range resulted in individual specialization in resource selection because of a patchy availability of particular resources across the landscape.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Differences in the selection of resources by individuals may be largely dependent on the availability or quality of the habitat (Gustine et al . ), and this was also reflected in the larger size of home ranges of wombats at higher altitudes (Matthews & Green ). The general geographic location of the wombat's home range resulted in individual specialization in resource selection because of a patchy availability of particular resources across the landscape.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the within‐home range resource selection of wombats in the subalpine zone of the Australian Snowy Mountains to provide a more detailed understanding of the habitats important to them, and to build a model of habitat suitability over the broader landscape, incorporating both the subalpine and alpine zones. Matthews and Green () found that wombat home range size increased with elevation, and building on this work, we hypothesized that differences in wombat spatial behaviour over an altitudinal gradient would lead to high variation in the selection of resources by individuals, but there would be commonalities for the most important resources at a population level. The main objectives of this study were to (i) develop estimates of habitat selection to determine which resources individual wombats were selecting relative to what was available, and (ii) identify resources selected across individuals, and map those resources over the landscape to predict areas of suitable wombat habitat in the subalpine and alpine zones.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations